On the role of affect and practice in the production of place - Duff, Cameron (2010)
Michel de Certeau's account of the modern city emphasises the 'doing' and 'making' residents undertake in an attempt to render a city more amenable to an 'art' of resistance. Yet, in attending to this doing and making, de Certeau has largely ignored the felt and affective dimensions of city life. Edward Casey provides a compelling means of interrogating these affective dimensions, distinguishing 'thick' and 'thin' places in everyday life. Thick places are contrived in the imbrications of affect, habit, and practice, presenting opportunities for personal enrichment and a deepening of affective experience. Casey's work restores the affective fecundity of place, even if it fails to provide a clear sense of how thick places might be identified. This paper takes up this challenge in an attempt to clarify the role of affect and practice in the production of place. The paper first reviews the practical and affective dimensions of this place-making before turning to an ethnographic account of young people, place, and urban life recently completed in Vancouver, Canada. This study explored the ways young people negotiate and transform place and the impact these practices have on the characteristic orientations of self and belonging. The experience of place was found to involve a series of affective relays between the cultivation of private places and the negotiation of designated spaces. The affective atmospheres created in these exchanges helped participants transform thin or designated spaces into dynamic thick places. The paper closes with a discussion of the role thick places might play in the design of innovative youth development efforts in urban settings. © 2010 Pion Ltd and its Licensors.